ANALYSIS OF VIBRATION CHARACTERISTICS OF THE PROJECTILE-BARREL COUPLING SYSTEM CONSIDERING THE INITIAL DEFLECTION OF THE BARREL - DI ChangChun; QIN JunQi; FANG Yu; YANG YuLiang (Jixie qiangdu)
In order to study the vibration characteristics of gun barrel under the action of moving projectile in gun launching process, taking an artillery gun for example, based on the Euler-Bernoulli beam theory, the coupled equations of vibration of a moving projectile elastic tube coupled with the initial deflection of the tube body are established. Using the finite element software ABAQUS and the dynamic analysis software ADAMS, the rigid flexible coupling dynamic model considering the initial deflection is established, and the numerical results are verified. On the basis of the model, the law of the muzzle velocity and the mass of the projectile affecting the muzzle vibration characteristics are analyzed. The results show that the initial deflection of the tube body has a great influence on the vibration analysis results, and can not be ignored. In the case of the initial deflection of the tube, the larger the projectile velocity is, the larger the muzzle vibration amplitude is. When the velocity is constant, the larger the projectile mass is, the larger the muzzle vibration amplitude is.